The Effect of Augmented Reality in Building Structure Learning on Civil Engineering Students' Conceptual Understanding - Satriawansyah, Tri; Dewi, Kemmala; Suparyanto, Tri; Santosa, Tomi Apra; Dewanto, Dewanto; Krisdiyanto, Aris; Wulandari, Andi Sri Rezky (Penerbit Widina, Widina Media Utama, 2024)
This study aims to determine the influence of the use of Augmented Reality in learning building structures on the understanding of concepts of Civil Engineering Students. This type of research is a quantitative research with a meta-analysis approach. The inclusion criteria in this study are research published in 2021-2024, research must be indexed by SINTA or Scopus, research must be relevant, research obtained from the journal databases of google scholar, Wiley, ScienceDirect, and ERIC and research data must be complete to calculate the effect size value (d). Data analysis with the help of the JASP application. The results of this study concluded that the 14 effects sizes analyzed had a total effect size value of d = 0.962; p 0.001. This finding explains that the use of Augmented Reality has a significant influence on the Conceptual Understanding of Civil Engineering Students in Building Structure Learning.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan Augmented Reality dalam pembelajaran struktur bangunan terhadap pemahaman konsep Mahasiswa Teknik Sipil. Jenis penelitian ini adalah penelitian kuantitatif dengan pendekatan meta-analisis. Kriteria inklusi dalam penelitian ini adalah penelitian diterbitkan tahun 2021-2024, penelitian harus terindeks SINTA atau Scopus, penelitian harus relevan, penelitian diperoleh dari database jurnal google scholar, Wiley, ScienceDirect, dan ERIC dan data penelitan harus lengkap untuk menghitung nilai effect size (d). Analisis data dengan bantuan aplikasi JASP. Hasil penelitian ini menyimpulkan bahwa 14 effects size yang dianalisis nilai summary effect size sebesar d = 0.962; p 0.001. Temuan ini menjelaskan bahwa penggunaan Augmented Reality memberikan pengaruh signifikan terhadap Pemahaman Konsep Mahasiswa Teknik Sipil dalam Pembelajaran Struktur Bangunan.